Analisis Profil Naratif Berbasis Gender: Aspek Produksi, Kompleksitas Sintaksis dan Penggunaan Bahasa pada Dewasa - Hanandita, Virginia (Jurnal Terapi Wicara dan Bahasa, 2025)
Background: Narrative analysis serves as a fundamental component in assessing language proficiency. From a Speech-Language Pathology (SLP) perspective, gender is considered a potential influencing factor on an individual's narrative profile, particularly affecting speech output and syntactic complexity. This study compared the narrative skills of adult male and female participants.Objectives: This research aims to analyze and compare the narrative skills of adult male and female participants by examining output quantity, syntactic complexity, and vocabulary usage in stories generated from the wordless picture book Frog, Where Are You?. Methods: This study utilized a descriptive qualitative approach with a comparative case study design. It involved two adult participants, one male and one female, both aged 34. Narrative data was collected using the wordless picture book "Frog, Where Are You?" and subsequently analyzed based on several parameters: the number and type of sentences, the frequency of borrowed vocabulary, and the use of narrative elements such as sound effects and embedded dialogue. Results: The findings reveal distinct narrative profiles. The male participant produces a higher quantity of output, which is dominated by simple sentences and features a high frequency of borrowed vocabulary and sound effects. Conversely, the female participant generates less output but demonstrates significantly greater syntactic complexity, employing more compound and complex sentences while using minimal borrowed vocabulary. Conclusion: This study concludes that clear differences exist in narrative profiles based on gender among adults. The male participant exhibits a report-oriented style emphasizing quantity, while the female participant demonstrates a rapport-oriented style characterized by superior syntactic complexity. These findings underscore the importance of considering gender as a variable in language assessments within speech-language pathology.   Keywords: Narrative Skills, Syntactic Complexity, Gender, Language Assessment, Frog Story